2002
DOI: 10.1097/00006676-200207000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Human Pancreatic Carcinoma Cell Growth and Invasion by Epigallocatechin-3-Gallate

Abstract: EGCG may be a potent biologic inhibitor of human pancreatic carcinomas, reducing their proliferative and invasive activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…Most cell culture (20)(21)(22)(23)38) and animal studies (24,25,39) in pancreatic cancer models support our results that high dietary intake of flavonols and flavan-3-ols might inhibit human pancreatic carcinogenesis. The exception is one Argentinean research group, which showed that dietary quercetin increases the incidence of pancreatic dysplastic foci in rats treated with the carcinogen nitrosomethylurea (40,41).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Most cell culture (20)(21)(22)(23)38) and animal studies (24,25,39) in pancreatic cancer models support our results that high dietary intake of flavonols and flavan-3-ols might inhibit human pancreatic carcinogenesis. The exception is one Argentinean research group, which showed that dietary quercetin increases the incidence of pancreatic dysplastic foci in rats treated with the carcinogen nitrosomethylurea (40,41).…”
Section: Discussionsupporting
confidence: 74%
“…Parsley, thyme, and celery are the primary dietary sources of the two major flavones apigenin and luteolin. Based on the protective effect of flavonoids against pancreatic carcinogenesis in most cell culture (20)(21)(22)(23) and animal studies (24,25), we hypothesized that high dietary intake of flavonols, flavan-3-ols, and flavones may inhibit development of exocrine pancreatic cancer in humans. The association between flavonoid intake and pancreatic cancer development has been evaluated in three prospective cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG also selectively inhibits COX-2 without affecting COX-1 expression (Hussain et al, 2005) and down-regulates K-ras (Lyn-Cook et al, 1999), suggesting its effects on the inactivation of oncogenes. Furthermore, the treatment of PANC1, Mia-PaCa-2, and BxPC-3 pancreatic cell lines with EGCG caused significant suppression of the invasive ability of the pancreatic cancer cells (Takada et al, 2002). These reports provide strong evidence in support of the roles of EGCG in chemoprevention and/or treatment of pancreatic cancer, especially because EGCG targets important cell signaling molecules as depicted in Figure 1.…”
Section: Egcgmentioning
confidence: 71%
“…Perhaps most notably, the anticancer properties of green tea flavanols have been reported in animal models and in human cell lines , as well as in human intervention studies [60]. On the other hand, green tea consumption has been proposed as significantly reducing the risk of cancer of the biliary tract [133], bladder [110], breast [74], and colon [72]. Many of the anti-cancer properties associated with green tea are thought to be mediated by the flavanol Epigallocatechin gallate (EGCG), which has been shown to induce apoptosis and inhibit cancer cell growth by altering the expression of cell cycle regulatory proteins and the activity of signaling proteins involved in cell proliferation, transformation, and metastasis [66].…”
Section: Antioxidants In Cancer Assaysmentioning
confidence: 99%